Thoughts on Coronavirus Disease 2019 Based on JingFang Medicine (Classical Chinese Formula) Solutions for COVID-19 - Huang Huang (Wolters Kluwer Health/LWW, 2020)
This article aims to provide some thoughts on the prevention and treatment of Coronavirus Disease 2019 (COVID-19) from the perspective of JingFang Medicine (Classical Chinese Formula). It is believed that the vague theoretical understanding of COVID-19 in Traditional Chinese Medicine does not hinder the precise treatment of the disease by following the rule of "With this Zheng, prescribe this Fang." According to the principle of "Fang-Zheng Correlation" and the knowledge gained from the thousands of years of experience in treating febrile diseases, Xiao Chai Hu Decoction (小柴胡汤) and its modifications are recommended with the emphasis on individualized treatment. As another form of practicing "Fang-Zheng Correlation," generalized group treatment should also be paid attention to. Giving considerations to the historical medical data, Jing Fang Bai Du Powder (荆防败毒散) and Shi Shen Decoction (十神汤) are recommended for group prevention treatment. Assisting the Zheng (Upright) Qi and using tonic formulas are two entirely different concepts. According to the principle of "Fang-Zheng Correlation," tonics abuse should be avoided in the prevention of COVID-19, and the using of Huang Qi (黄芪 Radix Astragali seu Hedysari) should also be very carefully done.